Curricular and Practical Considerations on Teacher Professional Development in Initial Teacher Training - Camus-Camus, Javiera (2023)
Objective. This article presents the results of a study, whose objective was to analyze the teacher professional development approach in its articulation with practical training, from the appropriation of teacher trainers and graduates, in four majors of a Chilean state university, located in the Valparaiso region. Methodology. Using a hermeneutic methodology of the interpretive paradigm of qualitative research, the study conducted a field work implying the content analysis of 37 documents –ministerial and institutional– and 16 semi-structured interviews with heads of degree departments, teachers of practice training and graduates. Results. Based on the methodological approach of grounded theory, the study analyzed the information collected and showed, as results, that the inicial training space presents guidelines in its institutional document system. These guidelines address the normatively established framework on teachers’ professional development, which do not materialize in the practical space of the majors, since, from the unified analysis of the discourse of interviewees, it can be argued that there is a curricular disarticulation that replicates a traditional training model from which knowledge is fragmented through the instrumentalization of pedagogical formation.